#### Answer

$= \frac{(x+2)}{-(x-7)}$

#### Work Step by Step

$\frac{(x+2)(x-5)}{(5-x)(x-7)}$
$= \frac{(x+2)(x-5)}{(-(x-5))(x-7)}$
$= \frac{(x+2)}{-(x-7)}$

Published by
Brooks Cole

ISBN 10:
0-53449-636-9

ISBN 13:
978-0-53449-636-4

$= \frac{(x+2)}{-(x-7)}$

$\frac{(x+2)(x-5)}{(5-x)(x-7)}$
$= \frac{(x+2)(x-5)}{(-(x-5))(x-7)}$
$= \frac{(x+2)}{-(x-7)}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.